Prospects and challenges of the textile industry of Bangladesh in reference with Chargeurs PCC (fashion technologies) - Bhuiyan, Sowda (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.